Toxicity of Tomato and Bell Pepper Insecticides/Miticides to Beneficial Insects - Mark A. Mossler (EDIS)
This document contains a table that presents categories that were either obtained from the Environmental Protection Agency, Kopperts Side-Effects Database, UF/IFAS Pest Management Strategic Plans, or label interpretation. When different categories are listed for different life stages (e.g. highly toxic in larval stage but nontoxic as an adult), the more toxic category has been placed in the table. This document is PI-90, one of a series of the Agronomy Department, UF/IFAS Extension. Published December 2005.